Design optimization of HRSG inlet duct geometry for improving flow uniformity using meta-heuristic algorithm - So, Hyun-Kyoo; Jo, Tae-Hyun; Lee, Yong-Han; Koo, Bon-Chan; Lee, Do-Hyung (Journal of mechanical science and technology, 2018)
The HRSG extensively affects all performance of CCPPs. The inlet duct geometry of an HRSG is the most essential part for determining heat exchange in the main body, in terms of flow uniformity. In the present study, numerical analysis of the HRSG flow characteristics and design optimization of inlet duct geometry for improving flow uniformity at the front section of the main body were performed to meet the trend requirements. A new inlet duct geometry, which has maximum flow uniformity, was proposed through design optimization procedures using a genetic algorithm. Specifically, the actual operating condition of the D-top model HRSG was applied and the pressure recovery coefficient and diffuser efficiency were considered. In the optimized design, a recirculation area was formed at the top internal wall of the second expansion stage. Results indicate that the forming of the recirculation area improves flow uniformity by rotating movement and spreading the high-speed flow.